2002
DOI: 10.1126/science.1073997
|View full text |Cite
|
Sign up to set email alerts
|

Instruction of Translating Ribosome by Nascent Peptide

Abstract: Expression of the tryptophanase operon of Escherichia coli is regulated by catabolite repression and tryptophan-induced transcription antitermination. An induction site activated by l-tryptophan is created in the translating ribosome during synthesis of TnaC, the 24-residue leader peptide. Replacing the tnaC stop codon with a tryptophan codon allows tryptophan-charged tryptophan transfer RNA to substitute for tryptophan as inducer. This suggests that the ribosomal A site occupied by the tryptophanyl moiety of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
218
0
7

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(237 citation statements)
references
References 27 publications
12
218
0
7
Order By: Relevance
“…Such nascent chain-exit tunnel interactions serve as a widespread and critical mechanism of gene regulation (1)(2)(3)(4)(5)(6). In this mode of regulation, translation is accompanied by ongoing negotiation between the tunnel and the nascent polypeptide, which is in turn affected by either the nascent chain's engagement in protein localization or concentration of an antibiotic or a metabolic compound.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such nascent chain-exit tunnel interactions serve as a widespread and critical mechanism of gene regulation (1)(2)(3)(4)(5)(6). In this mode of regulation, translation is accompanied by ongoing negotiation between the tunnel and the nascent polypeptide, which is in turn affected by either the nascent chain's engagement in protein localization or concentration of an antibiotic or a metabolic compound.…”
Section: Discussionmentioning
confidence: 99%
“…These studies revealed that the ribosome cannot necessarily complete translation of messages for any given amino acid sequences without any delay. Remarkably, programmed elongation arrest can serve as a novel mechanism of cellular regulation, for instance to monitor protein localization, metabolite concentration, and reception of an antibiotic (1)(2)(3)(4)(5)(6). Although regulatory nascent peptides having divergent stall-inducing amino acid sequences have been identified from different living organisms, their species-specificity and exchangeability among different systems have not been explored.…”
mentioning
confidence: 99%
“…1), one must consider the possible involvement of an additional mechanism(s) mediated by HCV core protein, such as selective translational inhibition of particular proteins, impaired intracellular/nuclear transport or impaired folding/maturation of certain proteins immediately after their synthesis. As for the selective translational inhibition of particular proteins, it was recently reported that a nascent peptide sequence of a bacterial protein could influence translation continuation or termination within a translating ribosome (11).…”
Section: Discussionmentioning
confidence: 99%
“…15 This tunnel was shown to undergo alterations associated with antibiotics resistant mutations, 55 to posses discriminating properties 35,56,57 and to actively participate in regulating intracellular cotranslational processes. [58][59][60] Experiments with the secM (secretion monitor) protein, 35 and the leader peptide of E. coli tryptophanase (tnaC) operon 57 are of particular interest. The sequences of both proteins contain a similar motif, which causes elongation arrest under specific conditions, in conjunction with the existence of cellular systems to which they belong.…”
Section: Tunnel Discrimination Of Nascent Proteinsmentioning
confidence: 99%